Language Policy and the Manufacturing of Consent for Foreign Intervention in Colombia - Valencia Marlon (Universidad Nacional de Colombia, 2013)
The present paper provides a critical analysis of Colombia's National Program of Bilingualism focusing on the ideologies behind it, how it facilitates the manufacturing of Colombian citizens' consent for foreign intervention through free trade agreements, and the progressive dismantling of public education. The program is analyzed with a critical language policy lens that brings into consideration the historical and socio-political factors of the Colombian context. For this purpose, several news articles, policy documents, and academic essays are discussed. Connections are made between this language policy, the interests of transnational companies, and how this policy helps portray the Colombian public education system as inadequate to fulfill the government's educational goals. El siguiente análisis crítico del Programa Nacional de Bilingüismo (PNB) en Colombia hace énfasis en las ideologías que hay detrás de dicho programa y como este facilita la fabricación del consentimiento de los ciudadanos colombianos para la intervención extranjera a través de los tratados de libre comercio, al igual que la privatización progresiva de la educación pública. Se analiza el programa de manera crítica teniendo en cuenta los factores históricos y sociopolíticos del contexto. Para este propósito se discuten artículos de noticias, documentos del programa y análisis académicos. El artículo establece relaciones entre el programa, los intereses de compañías multinacionales y la manera como dicha política lingüística pone de manifiesto la insuficiencia del sistema educativo público colombiano para alcanzar sus propias metas.